PREDICTIVE VALUE OF THE SIGNS AND SYMPTOMS PRECEDING ECLAMPSIA: A SYSTEMATIC REVIEW - Aromatika, Legina; Nofriyadi, Teddy; Juliana, Mutia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Malnutrition can be illness-related (one or more diseases or injuries directly result in nutrient imbalance), or it can be induced by environmental and behavioural variables associated with decreased nutrient intake and/or delivery. Comorbidities were shown to be related with child malnutrition in the study. Aim: The goal of this study is to showed predictive value of the signs and symptoms preceding eclampsia. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 88 articles, whereas the results of our search on SagePub brought up 43 articles. The results of the search conducted for the last year of 2013 yielded a total 13 articles for PubMed and 7 articles for SagePub. In the end, we compiled a total of 12 papers, 9 of which came from PubMed and 3 of which came from SagePub. We included five research that met the criteria. Conclusion: Visual abnormalities, epigastric discomfort, and headache are among of the most typically reported symptoms, however none of these were able to effectively predict or rule out the possibility of impending eclampsia.